Polysaccharide-based supramolecular gel polymer electrolyte based on high-concentration electrolyte system as well as preparation method and application of polysaccharide-based supramolecular gel polymer electrolyte

By introducing polysaccharides and ionic liquids in high -concentration electrolytes, the electrolyte electrolyte of super molecular gel polymerization is formed, and the problem of increased viscosity in the high concentration electrolyte system and decreased conductivity. Energy device.

CN119361337AActive Publication Date: 2025-01-24HANGZHOU NORMAL UNIVERSITY

Patent Information

Application Number
CN202411568406.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

While improving the voltage window and electrochemical properties of high-concentration electrolyte systems, there are problems of increasing viscosity and decreasing conductivity, resulting in poor electrode wetting and obstruction of liquid mass transfer.

Method used

Polysaccharide-based supramolecular gel polymer electrolyte (SGPE) is formed by introducing polysaccharide-based and ionic liquids such as hydroxypropyl chitosan (HPCS) and lithium bistrifluoromethanesulfonate imide (LiTFSI) into a high-concentration electrolyte. ), using the DMSO-Li+-TFSI-double bridge network structure and the hydrogen bonding and ion-dipole interaction of polysaccharide groups to construct a gel network with self-healing properties.

Benefits of technology

The mechanical performance of SGPE and the adjustability of conductive performance, improved LI+migration and electrode interface stability, overcome the high interface resistance problem, and obtained high power density and energy density energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361337A_ABST
    Figure CN119361337A_ABST
Patent Text Reader

Abstract

The invention discloses a polysaccharide-based supramolecular gel polymer electrolyte based on a high-concentration electrolyte system as well as a preparation method and application of the polysaccharide-based supramolecular gel polymer electrolyte, and the preparation method comprises the following steps: dissolving hydroxypropyl chitosan (HPCS) in dimethyl sulfoxide (DMSO) to prepare an HPCS-DMSO solution; the preparation method comprises the following steps: dissolving lithium bis (trifluoromethanesulfonic acid) imide (LiTFSI) into DMSO (Dimethylsulfoxide) to prepare a high-concentration LiTFSI-DMSO solution; and mixing the two solutions to obtain the polysaccharide-based supramolecular gel polymer electrolyte, wherein the prepared gel can be used for preparing an energy storage device. According to the present invention, the groups having interaction with the anions and the solvent molecules are pertinently introduced into the polymer, and the double-bridging structure formed by the anion-Li < + >-solvent molecules is utilized to slow down the diffusion of the anions and achieve the Li < + > rapid transition mode, such that the Li < + > migration number in the gel network and the electrode interface stability are improved, and the wide application prospect is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy storage, and relates to a polysaccharide-based supramolecular gel polymer electrolyte based on a high-concentration electrolyte system, a preparation method and an application thereof, and in particular to a polysaccharide-based supramolecular gel polymer electrolyte (SGPE) based on a LiTFSI-DMSO high-concentration electrolyte system (High Concentration Electrolytes, HCE), a preparation method thereof and an application thereof in preparing an energy storage device. Technical Background With the popularity of portable electronic products and electric vehicles, the research and development of energy storage devices with high energy density, high power density and long cycle life is a research hotspot in the field of new energy. Supercapacitors have attracted widespread attention due to their high power density, fast charge and discharge rate, and long cycle life, but their energy density is lower than that of batteries, which restricts their widespread application. It is well known that the energy density of capacitors mainly depends on the capacity and voltage window of the electrode material itself. Therefore, in addition to developing positive and negative electrode materials with high specific energy, broadening the working voltage window of capacitors is also an effective means to effectively improve the energy density of capacitors.

[0003] At present, the general strategy is to use organic electrolytes or ionic liquids to replace aqueous electrolytes to increase the voltage window, especially high concentration electrolyte (HCE) systems. Since there are a large number of contact ion pairs and aggregates in the electrolyte, and free solvent molecules are almost non-existent, the stability of the positive and negative electrode interfaces can be significantly improved. For example, studies have shown that concentrated fluoride anions (TFSI - ) can form a LiF-rich SEI passivation layer at the negative electrode, thereby widening the electrochemical stability window and battery operating voltage, thereby improving the electrochemical performance of the device. However, as the concentration of the electrolyte increases, the solvent molecules in the system are limited, the interaction between the positive and negative ions of the electrolyte increases, and the ion migration is hindered, which inevitably leads to an increase in viscosity and a decrease in conductivity. For example, the commonly used 1 mol·L -1 The ionic conductivity and viscosity of LiPF6 / EC-DEC electrolyte are ~10 mS·cm -1 and ~3 mPa·s, which have excellent mass transfer capacity and liquid fluidity. In contrast, high-concentration electrolytes such as 4 mol·L -1 The ionic conductivity of LiFSI-DME is only 5.7 mS·cm -1, the viscosity is as high as 30 mPa·s, which is ten times that of traditional dilute solutions. This makes high-concentration electrolytes generally have application challenges such as poor electrode wettability and obstructed liquid phase mass transfer.

[0004] Sulfone solvents with high intrinsic viscosity (such as sulfolane SL, dimethyl sulfoxide DMSO, etc.) are used in lithium metal batteries, especially high-voltage batteries, thanks to the unique solvation structure and interface stabilization mechanism of HCE. It is worth noting that even under the condition of limited overall ionic conductivity of HCE, the HCE electrolyte system of LiBF4-SL also shows high Li + The migration number meets the needs of high-rate applications. The study found that this is mainly due to the SL solvent molecules and BF4 - The anion can act as a bridging ligand to complex two Li + , forming a unique SL-L i+ -BF4 - Double-bridged network solvation structure, Li + The transport mode in the solution changes from the diffusion mode common in dilute solutions to the hopping conduction mechanism. + Dynamic ligand exchange between solvent molecules and anions enables Li + However, as an organic solvent electrolyte system, there are always safety risks such as liquid leakage and explosion.

[0005] Supramolecular gel polymer electrolyte (SGPE) has a three-dimensional network structure, which can encapsulate the electrolyte solution to prevent leakage risk. Unlike traditional covalent bond polymer gels, supramolecular gels are molecules that self-assemble through non-covalent interactions to form a three-dimensional network, which generally has self-healing properties. Compared with polymer solid electrolytes, there are a certain amount of solvent molecules in SGPE, which provides a continuous conductive channel for ion conduction migration, so that it has polymer network support performance while showing faster ion conduction performance than solid electrolytes. However, due to the existence of the cross-linked structure of polymer molecules, the mobility of polymer chain segments is limited, which will cause the ion migration ability to be 1~2 orders of magnitude lower than that of solution electrolytes. Therefore, the design and preparation of high Li + The migration number of GPE (Gel Polymer Electrolyte) is currently a hot topic in research in this field. Summary of the invention

[0006] An object of the present invention is to address the deficiencies of the prior art and to provide a method for preparing a polysaccharide-based supramolecular gel polymer electrolyte based on a high-concentration electrolyte system, the mechanical properties and conductive properties of which are adjustable and can be recycled and reused.

[0007] The present invention achieves the above object through the following technical solutions: Step (1), dissolving hydroxypropyl chitosan (HPCS) in dimethyl sulfoxide (DMSO) to prepare an HPCS-DMSO solution; the concentration of the HPCS-DMSO solution is 0.01-0.40 g / mL.

[0008] Step (2), dissolving lithium bis(trifluoromethanesulfonic acid) imide (LiTFSI) in dimethyl sulfoxide (DMSO) to prepare a LiTFSI-DMSO solution; the concentration of the LiTFSI-DMSO solution is 4-12 mol / L; Step (3), at room temperature, mixing the HPCS-DMSO solution and the LiTFSI-DMSO solution in a volume ratio of 1:3 to 3:1, stirring evenly and then standing at room temperature for 24 to 72 hours to obtain a polysaccharide-based supramolecular gel polymer electrolyte.

[0009] The molecular formula of HPCS is:

[0010] Among them, x, y, and z are all greater than 1.

[0011] Preferably, the HPCS has a number average molecular weight of 10,000 g / mol to 500,000 g / mol, a degree of deacetylation of 55% or more, a degree of hydroxypropyl substitution of 50% to 90%, and a molecular weight of 1.0×10 4 ~5.0×10 5 .

[0012] The molecular formula of LiTFSI is:

[0013] Preferably, the concentration of the HPCS-DMSO solution is 0.05-0.20 g / mL; Preferably, the concentration of LiTFSI-DMSO solution is 5-10 mol / L; Preferably, the volume ratio of the HPCS-DMSO solution to the LiTFSI-DMSO solution is 1:1.

[0014] Preferably, the stirring rate in steps (1) and (2) is 500-600 rpm. The reaction temperature is related to the molecular weight of HPCS and the amount of LiTFSI added. HPCS molecular weight and LiTFSI added in a lower amount are soluble at room temperature, while higher amounts require heating to dissolve. The reaction temperature is preferably 25-70°C.

[0015] The present invention utilizes DMSO-Li + -TFSI --The double-bridged network solvation structure forms hydrogen bonds and ion-dipole interactions with the abundant -OH and -COC groups in the HPCS molecular chain, realizing the construction of SGPE.

[0016] Another object of the present invention is to provide a quasi-solid gel electrolyte of HCE based on DMSO-LiTFSI, which is prepared by the above method.

[0017] Another object of the present invention is to provide the use of the above-mentioned quasi-solid gel electrolyte based on natural polysaccharide-ionic liquid in the preparation of energy storage devices, the energy storage devices include supercapacitors, secondary lithium batteries, etc., and relate to a method for preparing gel electrolyte in situ on the electrode surface at room temperature, specifically: using an electrode sheet as a substrate, a certain amount of LiTFSI-DMSO solution and a certain concentration of HPCS-DMSO solution are evenly coated on the electrode surface by a pipette gun, and in situ gelation on the electrode surface can be achieved. If there are requirements for the size and shape of the gel electrolyte, a silicone or PTFE mold of designed size and shape can be placed on the electrode surface, and LiTFSI and HPCS-DMSO solution can be added to the inner cavity of the mold.

[0018] Compared with the prior art, the present invention has the following advantages: (1) The present invention specifically introduces groups such as hydroxyl and hydroxypropyl that interact with anions and solvent molecules (hydrogen bonds, electrostatic interactions, etc.) into the polymer. On the one hand, the three-dimensional polymer network is constructed through intermolecular interactions. The gel network has self-healing properties. On the other hand, an anion-Li + -The double-bridged structure of the solvent molecules slows down the diffusion of anions while achieving similar Li + Li in high concentration electrolyte system + Fast transition mode improves Li + The migration number and electrode interface stability can obtain energy storage devices with high power density and energy density.

[0019] (2) The present invention uses DMSO as a solvent. The sulfone functional group of DMSO has a strong electron-withdrawing ability and a low HOMO energy level. Therefore, compared with other commonly used electrolyte solvents such as carbonate solvents, DMSO has higher oxidation stability.

[0020] (3) The supramolecular gel precursors HPCS-DMSO solution and LiTFSI-DMSO provided by the present invention have good wetting properties for common electrode materials (porous carbon, lithium cobalt oxide, lithium iron phosphate, etc.), and can realize the in-situ preparation of gel on the surface of electrode materials. The obtained polymer electrolyte can effectively fill the voids on the electrode surface, thereby achieving close contact between the gel electrolyte and the electrode material, thereby effectively overcoming the problem of high interface resistance.

[0021] (4) The gel electrolyte preparation technology provided by the present invention is simple and easy to operate, does not involve the use of chemical cross-linking agents and photothermal polymerization reaction processes, and is conducive to the large-scale batch preparation of gel electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the principle of the present invention; Figure 2 This is a digital photo of the gel obtained in Example 4; Figure 3 is the infrared spectrum of the gel obtained in Example 4; Figure 4 The rheological behavior diagram of the gel obtained in Example 4 under low shear strain (1%) and high shear strain (700%); Figure 5 The graphs show the changes of storage modulus (G′) and loss modulus (G′′) of the gel samples of Examples 1-10 prepared with solutions of different LiTFSI concentrations and different HPCS concentrations at 5% deformation with shear frequency; wherein (a) represents different LiTFSI concentrations, and (b) represents different HPCS concentrations.

[0023] Figure 6 Digital photographs, cross-sectional SEM images and local magnified images of original glass fiber (GF) and gel formed in situ on GF, where (a1) is a digital photograph of GF, (a2) is an image of (a1) at a magnification of 1000 times, and (a3) ​​is an image of (a1) at a magnification of 40000 times; (b1) is a digital photograph of gel formed in situ on GF, (b2) is an image of (b1) at a magnification of 1000 times, and (b3) is an image of (b1) at a magnification of 40000 times.

[0024] Figure 7 The figure is an AC impedance diagram of an electrical double-layer capacitor (EDLC) assembled using the gel obtained in Example 4 as the electrolyte. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to the scope of the specific embodiments.

[0026] like Figure 1 As shown, the present invention provides a method for preparing a polysaccharide-based supramolecular gel polymer electrolyte of a high-concentration electrolyte system, comprising the following steps: Step (1), HPCS and DMSO are mixed in a certain ratio at 70°C and 500 rpm to prepare an HPCS-DMSO solution.

[0027] The HPCS has a number average molecular weight of 10,000 g / mol to 500,000 g / mol, a deacetylation degree of 55% or more, a hydroxypropyl substitution degree of 50% to 90%, and a molecular weight of 1.0×10 4 ~5.0×10 5 .

[0028] Step (2), LiTFSI and DMSO are mixed in a certain ratio at 70°C and 500 rpm to prepare a LiTFSI-DMSO solution.

[0029] The molecular weight of the LiTFSI is 287.08 g / mol.

[0030] Step (3), at room temperature, use a syringe to take a certain amount of the above HPCS-DMSO solution and LiTFSI-DMSO solution, add them dropwise into a plastic test tube, stir evenly and place at room temperature for 24-72 hours to obtain a self-assembled gel electrolyte.

[0031] Example 1 Step (1), 0.14 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.14 .

[0032] Step (2), 1.435 g LiTFSI and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 5 mol / L, denoted as LiTFSI5.

[0033] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 72 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.07 -LiTFSI 2.5 .

[0034] Step (1), 0.14 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.14 .

[0035] Step (2), 1.722 g LiTFSI and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 6 mol / L, which was recorded as LiTFSI6.

[0036] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 48 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.07 -LiTFSI3.

[0037] Example 3 Step (1), 0.14 g hydroxypropyl chitosan (HPCS) and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.14 .

[0038] Step (2), 2.010 g LiTFSI and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 7 mol / L, which was recorded as LiTFSI7.

[0039] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 24 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.07 -LiTFSI 3.5 .

[0040] Example 4 Step (1), 0.14 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.14 .

[0041] Step (2), 2.300 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 8 mol / L, which was recorded as LiTFSI8.

[0042] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 24 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.07 -LiTFSI4.

[0043] Figure 2 HPCS 0.07-Optical photograph of LiTFSI4 sample, the gel is transparent and self-supporting.

[0044] Example 5 Step (1), 0.10 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.10 .

[0045] Step (2), 1.435 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 5 mol / L, which was recorded as LiTFSI5.

[0046] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 72 hours to obtain a self-assembled gel electrolyte, denoted as HPCS 0.05 -LiTFSI 2.5 .

[0047] Example 6 Step (1), 0.12 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.12 .

[0048] Step (2), 1.435 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 5 mol / L, which was recorded as LiTFSI5.

[0049] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 72 hours to obtain a self-assembled gel electrolyte, denoted as HPCS 0.06 -LiTFSI 2.5 .

[0050] Example 7 Step (1), 0.06 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.06 .

[0051] Step (2), 2.300 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 8 mol / L, which was recorded as LiTFSI8.

[0052] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 72 hours to obtain a self-assembled gel electrolyte, denoted as HPCS 0.03 -LiTFSI4.

[0053] Example 8 Step (1), 0.08 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.08 .

[0054] Step (2), 2.300 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 8 mol / L, which was recorded as LiTFSI8.

[0055] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 72 hours to obtain a self-assembled gel electrolyte, denoted as HPCS 0.04 -LiTFSI4.

[0056] Example 9 Step (1), 0.10 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.10 .

[0057] Step (2), 2.300 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 8 mol / L, which was recorded as LiTFSI8.

[0058] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 48 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.05 -LiTFSI4.

[0059] Example 10 Step (1), 0.12 g HPCS and 1 mL DMSO were prepared at 70 °C and 500 rpm to prepare a yellow transparent HPCS-DMSO solution, denoted as HPCS 0.12 .

[0060] Step (2), 2.300 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 mL of DMSO were prepared at 70 °C and 500 rpm to prepare a colorless and transparent LiTFSI-DMSO solution with a concentration of 8 mol / L, which was recorded as LiTFSI8.

[0061] Step (3), at room temperature, use a syringe to take 1 mL of the above HPCS-DMSO solution and LiTFSI-DMSO solution respectively, add them dropwise into the test tube, stir evenly and place at room temperature for 24 h to obtain a self-assembled gel electrolyte, denoted as HPCS 0.06 -LiTFSI4.

[0062] Test Example 1 The HPCS gel obtained in Example 4 0.07 -LiTFSI4 was characterized by infrared structure, and the results are as follows Figure 3 As shown in the figure, it can be seen that HPCS 0.07 -LiTFSI4 gel at 3582 cm -1 The -OH and -NH2 absorption peaks of HPCS polysaccharide appeared, which were consistent with the 0.07 Solution (3457 cm -1 ), the absorption peak position has a significant blue shift, which may be due to the coordination effect between LiTFSI and -OH and -NH2 with the introduction of LiTFSI. -1 and 1133 cm -1 The absorption peak at is attributed to the O=S=O stretching vibration peak in the TFSI anion. Compared with LiTFSI4, the absorption peak position is red-shifted, which may be caused by the hydrogen bond interaction between CF in LiTFSI and -OH in the polysaccharide.

[0063] The HPCS prepared in Example 4 was subjected to rheological tests. 0.07-LiTFSI4 was subjected to alternating low shear stress and high shear stress cycles. The results are as follows Figure 4 As shown in the figure, when the shear strain increases from 1% to 700%, the storage modulus (G′) and loss modulus (G′′) of the gel decrease rapidly. When the shear strain decreases to 1%, G′ and G′′ quickly return to their original values. This shear recovery behavior can be observed in repeated cycles, indicating that the gel material has excellent self-healing properties, and the healing process does not require external stimulation, showing a self-healing effect.

[0064] The rheological method was used to investigate the changes of G′ and G′′ with shear frequency d under 5% deformation of the gel samples prepared in Examples 1-10. The results are as follows: Figure 5 As shown. Figure 5 (a) It can be seen that as the concentration of LiTFSI-DMSO increases, the storage modulus of the gel increases; Figure 5 (b) It can be seen that as the concentration of HPCS-DMSO increases, the storage modulus of the gel increases.

[0065] Application Example: Example 4 was selected to carry out the electrochemical performance experimental test of the double-layer supercapacitor.

[0066] a. Preparation of electrode sheets: Activated carbon YP50, acetylene black, and PVDF were mixed in an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to obtain a uniform mixed slurry. The slurry was then evenly applied to the carbon-coated aluminum foil with a scraper and dried in a vacuum oven at 110 °C for 12 h. Finally, the electrode sheet was cut into a circular electrode with a diameter of 12 mm. The loading amount of active material was about 1.2 mg / cm 2 .

[0067] b. Preparation of gel electrolyte: Using glass fiber diaphragm as support membrane, gel electrolyte is prepared on the diaphragm for subsequent assembly and testing of button-type supercapacitors. First, use a syringe to take 0.1 mL of HPCS in Example 4. 0.14 After the glass fiber separator was completely soaked, 0.1 mL of LiTFSI8 in Example 4 was taken with a syringe and dropped onto the glass fiber separator. The mixture was then placed at room temperature for 24 h to obtain a gel electrolyte with the glass fiber separator as the support membrane, which was recorded as GF-HPCS. 0.07 -LiTFSI 4。 (All the above operations are completed in the glove box).

[0068] Original GF and GF-HPCS formed in situ on GF 0.07-LiTFSI4 digital photos, cross-sectional scanning electron microscope images (magnification 1000 times) and local magnification images (magnification 40000 times) are shown as follows Figure 6 (a1) and Figure 6 (b1), Figure 6 (a2) and Figure 6 (b2), Figure 6 (a3) and Figure 6 (b3) is shown.

[0069] c. Assembly of supercapacitor: In a glove box, 2032 button cell negative electrode shell, spring, stainless steel sheet, electrode sheet, gel electrolyte (GF-HPCS 0.07 -LiTFSI4), electrode sheet, stainless steel sheet, and 2032 button battery positive electrode shell are assembled in sequence, and then placed on a button battery sealing machine for packaging to obtain a button double-layer supercapacitor. Its AC impedance diagram is shown in Figure 7 shown.

[0070] d. Electrochemical window (LSV) test: The supercapacitor was tested by LSV using an Autolab electrochemical workstation with two stainless steel sheets as the working electrode and the counter electrode. The scan rate was 5 mV / s and the scan potential range was -2 V to 3 V. The LSV results showed that the electrochemical window of the supercapacitor was 3 V.

[0071] e. Cyclic voltammetry (CV) test: The supercapacitor was tested by CV using the Autolab electrochemical workstation with a scan rate of 30 mV / s. The supercapacitor was tested in the voltage ranges of 0-2 V, 0-2.5 V, 0-2.7 V, and 0-3 V. When the operating voltage increased to 2.7 V, the CV curve of the supercapacitor showed a quasi-rectangular shape, indicating that it was an ideal double-layer supercapacitor. When the operating voltage increased to 3 V, polarization occurred and the CV curve deviated from the rectangular shape, so 2.7 V was the maximum operating voltage of the supercapacitor. In the 0-2.7 V operating voltage window, the supercapacitor was scanned at a speed from 5 mV / s to 100 mV / s, and the CV curves showed good symmetry and quasi-rectangular shapes, indicating that the supercapacitor had an ideal double-layer capacitance behavior.

[0072] f. Constant current charge and discharge (GCD) test: The GCD test of the supercapacitor was carried out using the Autolab electrochemical workstation. In the working voltage window of 0-2.7 V, the current density was set from 1 A / g to 7 A / g. The results showed that the supercapacitor had a typical triangular GCD curve when the current density changed from 1 A / g to 7 A / g. The symmetrical triangle shape indicated that there was a reversible charge and discharge process at the interface between the electrode and the electrolyte, achieving an ideal double-layer capacitance behavior. The specific capacitance (C) of the supercapacitor was calculated from the GCD curve according to formula (1): the specific capacitance (C) of the supercapacitor corresponding to the current density of 1 A / g, 3 A / g, 5 A / g, and 7 A / g was 89.6 F / g, 80.7 F / g, 76.0 F / g, and 69.9 F / g. The energy density and power density of the supercapacitor at different current densities are calculated based on the specific capacitance using formulas (2) and (3) (Table 1). At a current density of 1 A / g, the energy density of the supercapacitor is 19.4 Wh / kg and the power density is 624.9 W / kg.

[0073] Specific capacitance: (1) Energy density: (2) Power density: (3) Where: C is the specific capacitance is the discharge time m is the mass of active material in a single electrode V is the discharge voltage, E is the energy density, and P is the power density. Table 1

[0074] g. Electrochemical impedance spectroscopy (EIS) test: The supercapacitor was tested using an Autolab electrochemical workstation with a voltage amplitude of 10 mV and a frequency range of 10 -1 -10 5 The results are as follows Figure 7 As shown. The EIS curve is semicircular at high frequencies, which is consistent with the energy storage characteristics of the activated carbon electrode; it is almost a vertical line at low frequencies, indicating that the diffusion of ions on the activated carbon electrode has a small impedance. The intersection of the curve and the real axis in the high-frequency region indicates that the equivalent series resistance (Res) of the supercapacitor is 12.4Ω, and the diameter of the semicircle indicates that the charge transfer resistance is 12.3Ω.

[0075] f. Lithium ion migration number ( ) Test: Use Autolab electrochemical workstation to assemble Li / / Li symmetrical battery, and use DC polarization and AC impedance combination method to test , the frequency range of the AC impedance test is 1000 kHz~0.1 Hz, ΔV=0.01V is set, and the test time is 6400 s. Calculate according to formula (4): is 0.51.

[0076] in: is the initial current, is the steady-state current, and are the initial interface resistance and the steady-state resistance after polarization, respectively.

Claims

1. A method for preparing a polysaccharide-based supramolecular gel polymer electrolyte based on a high-concentration electrolyte system, characterized in that: The method comprises the following steps: Step (1), dissolving HPCS in DMSO to prepare an HPCS-DMSO solution; the molecular formula of the HPCS is:

2. Among them, x, y, and z are all greater than 1; Step (2), dissolving LiTFSI in DMSO to prepare a LiTFSI-DMSO solution; the concentration of the LiTFSI-DMSO solution is 4-12 mol / L; Step (3), at room temperature, mixing the HPCS-DMSO solution and the LiTFSI-DMSO solution, stirring evenly and then standing at room temperature to obtain a polysaccharide-based supramolecular gel polymer electrolyte.

3. The preparation method according to claim 1, characterized in that: The number average molecular weight of the HPCS is 10,000 g / mol to 500,000 g / mol.

4. The preparation method according to claim 2, characterized in that: The HPCS has a deacetylation degree of 55% or more, a hydroxypropyl substitution degree of 50% to 90%, and a molecular weight of 1.0×10 4 ~5.0×10 5 .

5. The preparation method according to claim 1, characterized in that: The concentration of the HPCS-DMSO solution is 0.01-0.40 g / mL.

6. The preparation method according to claim 1, characterized in that: The concentration of the LiTFSI-DMSO solution is 5-10 mol / L. The preparation method according to claim 1, characterized in that the volume ratio of the HPCS-DMSO solution to the LiTFSI-DMSO solution is 1:3~3:

1.

7. The preparation method according to claim 1, characterized in that: The standing time of step (3) is 24-72 hours.

8. A polysaccharide-based supramolecular gel polymer electrolyte based on LiTFSI-DMSO, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the polysaccharide-based supramolecular gel polymer electrolyte as claimed in claim 8 in the preparation of an energy storage device.

10. The use according to claim 9, characterized in that: The energy storage device includes a supercapacitor and a secondary lithium battery.

Citation Information

Patent Citations

  • High-performance all-solid-state supercapacitor based on gel polymer electrolyte and preparation method thereof

    CN113035583A

  • Preparation method and application of chitosan-based composite organic ionic liquid gel electrolyte

    CN116313557A

  • Quasi-solid gel electrolyte based on natural polysaccharide-ionic liquid, preparation method of quasi-solid gel electrolyte and application of quasi-solid gel electrolyte in preparation of energy storage device

    CN118039368A

  • Li-CO2 battery and electrolyte thereof

    CN118231774A

Cited By

  • Lithium metal battery as well as high-voltage wide-temperature-range gel polymer electrolyte, preparation method and application thereof

    CN121416596A